Stać się sobą. O Narcyzie - Graczyk, Ewa (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The author analyzes and interprets the style, structure, and narration in the novel that marked the transition in Nałkowska’s fiction from the Young Poland phase to the inter-war phase. The author shows the place of the novel in Nałkowska’s work, presenting the links with the work of other women writers of the 19th century, especially Orzeszkowa and Zapolska. The author attempts to demonstrate that Narcyza’s features elements of novelistic, feminine polyphony and irony (thanks to the use of the work of literary mothers); such elements were rare in the novelists earlier texts. The second part of the article is devoted to the analysis of the main heroine; the author demonstrates that Nałkowska wants to make the character a problematic and ideological heroine in the Bakhtinian sense. The author analyses the novelist’s techniques of “advancing” Narcyza, and the attempts to extricate the heroine, who is a marriageable maid, from the romance-like situation and to turn her into a serious character in the sense that used to be exclusively possible for male characters.